Numerical modelling of multibeam accelerating structures - Gavrilov, N.M.; Komarov, D.A.; Bogachenkov, D.A.; Strukov, J.N. (Вопросы атомной науки и техники, 2004)
The three-dimensional multibeam numerical simulation has been carried out on the basis of integral equations. Dispersion equations and expressions for shunt impedance and Q-factor have been obtained for E and H oscillations in cylindrical cavities. The tensor Green function and filament-like representation of the beam were used.